Consumer acceptance of fuel-cell systems in electronic products. (1st January 2013) - Flipsen, Bas; Spitas, Christos; Raangs, Anne
Introducing a fuel-cell powered power source in a portable electronic device could increase the run time of the device. It will also introduce problems such as higher run costs. One important property for the user when he/she is buying a device is the 'runtime on one charge'. Batteries are limited in this and the time-to-use on a full charge is decreasing with increasing functionality. When the user is making the transition to fuel-cells, he/she has to be willing to change their behaviour from grid-connected to cartridge-based charging. This paper investigates the willingness of the consumer to change to a cartridge-based electronic device. To test the willingness of the consumer, the conjoint analysis is used and the results show that the user finds volume the most important property influencing his/her buying behaviour. This research also shows the value and limitations of the conjoint analysis as a tool to evaluate new technologies.